Evaluation of Integrated Arterial Filter Oxygenator vs. External Arterial Filters on Clinical Outcomes and Neurocognitive Function in Pediatric Cardiac Surgery: A Prospective Randomized Controlled Trial (RCT) - Vishal Vinayak Bhende; Mathangi Krishnakumar; Dushyantkumar Mukundbhai Parmar; Arunkumar Ghanshyambhai Rudakiya; Tanishq Shashikant Sharma; Amit Kumar; Paresh Dilip Nerurkar; Saptak Piyush Mankad; Mamta Roshan Patel (Health Science Reports)
ABSTRACT Background and Aims Innovative advancements in cardiopulmonary bypass (CPB) configurations, such as surface coating, blood filtration, and miniaturization, aim to reduce gaseous microemboli (GME) that contribute to embolic organ damage, particularly neurological dysfunction. Arterial line filters are effective in mitigating embolism risk. Neurological complications post‐cardiac surgery can result from reduced cerebral blood flow, embolic materials, and other factors, including anesthesia. This study evaluates the impact of integrated arterial filter oxygenator (IAF‐Oxy.) versus external arterial filters (EAF) on clinical outcomes in pediatric patients undergoing surgery for congenital heart disease (CHD). Methods This prospective randomized controlled trial included 100 pediatric patients undergoing cardiac surgery under CPB. Patients were randomized into two groups: Group A included external arterial filters (EAF) with membrane oxygenators such as Capiox Baby RX 05 and others, while Group B included integrated arterial filters (IAF) with oxygenators like Capiox Baby FX 05. The outcomes were neurological function, mechanical ventilation time (hours), intensive care unit stay (hours), and hospital stay (days). Results Group B demonstrated significantly lower mean aortic cross‐clamp (70.2 ± 38.5 vs. 88.0 ± 49.7 min; p = 0.04) and CPB times (104 ± 48.1 vs. 128 ± 66 min; p = 0.03). Postoperative FOUR scores were identical (16 out of 16) in both groups. Median ventilation time (26.5 [24.25–125.25] hours in Group A vs. 25.0 [12.0–50.0] hours in Group B; p = 0.258), CSICU stay (120.0 [72.0–216.0] hours in Group A vs. 108.0 [72.0–162.0] hours in Group B; p = 0.358), and hospital stay (13 ± 11 days in Group A vs. 10 ± 5 days in Group B; p = 0.138) were comparable between groups. Conclusion Integrated arterial filter oxygenator may serve as an alternative to external arterial filters, potentially reducing gaseous microemboli. IAF‐Oxy. could improve clinical outcomes, reduce CSICU and hospital stays, and enhance care for pediatric congenital heart disease (CHD) patients.